Teachers’ resilience in facing workload adversities in times of pandemic: The case of the private school teachers in a developing country - Christian L. Banal; Ruth A. Ortega-Dela Cruz (Indonesian Journal of Social Sciences, 2022)
This case study used a combination of quantitative and qualitative methods to determine the resilience of private school teachers in facing workload adversities during the COVID-19 pandemic in Academic Year 2020-2021. It also analysed how the teaching workload adversities affect the teachers’ teaching performance in terms of assigned classes and school-related activities, and teacher well-being in terms of teaching activities, non-teaching activities, and well-being. Resilience was determined using the Adversity Response Profile (ARP) developed by Dr. Paul Stoltz, the proponent of Adversity Quotient. Findings showed that the mean of respondents’ ARP is Below Average. This in addition to heavy and challenging teaching workloads has negative impacts on the teachers’ teaching performance and well-being. The study provides implications not only to its subjects but to all stakeholders of an educational institution. It signifies the importance of resilience or the ability to bounce back from adversities in life. Now that the COVID-19 pandemic persists, having resilience is a must especially for teachers. Thus, it calls for a more administrative support by providing the ways and means to help develop and strengthen the teachers’ resilience especially in this time of pandemic.